2010
DOI: 10.1088/0022-3727/43/31/315204
|View full text |Cite
|
Sign up to set email alerts
|

Streak investigations of the initial phase of a subnanosecond pulsed electrical breakdown of high-pressure gas gaps

Abstract: The initiation and the development of a breakdown of highly overvoltaged high-pressure (from 4 to 40 atm) gas gaps by voltage pulses having the risetime of 1 ns or shorter are studied experimentally and in theoretical terms. The study revealed that ionization processes leading to the breakdown start in the gas volume and not from the surface of the electrodes. The gap flashover is followed by ionization wave processes initiating in the gas volume and playing the decisive role at the first phase of the breakdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 22 publications
0
18
0
4
Order By: Relevance
“…Here let us note that, in general, also background electrons with density ≤ 10 3 cm -3 that exist naturally in gas 19 could become RAE. 23 However, the simulations showed that these electrons left the cathode region r < 14µm at an earlier time when E c < E cr . Thus, these background electrons cannot be considered as the source of RAE.…”
Section: Resultsmentioning
confidence: 93%
“…Here let us note that, in general, also background electrons with density ≤ 10 3 cm -3 that exist naturally in gas 19 could become RAE. 23 However, the simulations showed that these electrons left the cathode region r < 14µm at an earlier time when E c < E cr . Thus, these background electrons cannot be considered as the source of RAE.…”
Section: Resultsmentioning
confidence: 93%
“…В ряде работ были проведены исследования динамики свечения плазмы в промежутке [3,6,8,10,11,13,17,21,24]. Так, в работе [3] было показано, что в воздухе атмосферного давления при положительной полярности импульсов напряжения (U = 43 kV, τ 0.5 = 12 ns, τ 0.1−0.9 = 2−3 ns), подаваемых на острийный электрод, свечение плазмы возникает вблизи острийного электрода и имеет форму, близкую к шару.…”
Section: Introductionunclassified
“…Generation of runaway (fast) electrons and X-ray radiation essentially influences the breakdown of the gaps with electrodes having a small radius of curvature; see papers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] published in recent years and references in [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Electric field amplification in high-pressure gases results in generation of electric fields which are sufficient for appearance of the first fast electrons due to a field emission.…”
Section: Introductionmentioning
confidence: 99%